THE EFFECTS OF CIRCUIT TRAINING PROGRAM ON CARDIOVASCULAR ENDURANCE BY WOMEN COLLEGE STUDENTS - ali, syed kamaruzaman syed; s g, ch'ng; hidayat, yusup (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2011)
The recommended rate of physical activity is at least 30 minutes of moderate intensity physical activity, preferably done at least 3 times a week, to increase and maintain individual health related fitness (ACSM, 1998). Hence, in this study, the researcher investigates the effects of an intervention program using 10 – 15 minutes of circuit training program (physical conditioning) for the duration of 10 weeks during the sports athletics co-curriculum activities to enhance health related fitness (cardiovascular endurance) by college students. Therefore, this study is to investigate the effectiveness of intervention program towards the level of health-related fitness (cardiovascular endurance) using the fitness test.The purpose of this study is to investigate the effects of circuit training program (circuit training) on health related fitness (cardiovascular endurance) by 60 women college students. A quasi experimental design was adapted for this study, using pretest-posttest control group design, which uses circuit training as independent variable, while dependent variable are health-related fitness test instruments namely cardiovascular endurance (12 minutes run).Before the commencement of the study, an independent T-test analysis was conducted on the pretest data of both groups. It was found that there was no statistically significant different in the mean scores between control group and experimental group (1298.33 + 171.95, 1230.00 + 138.71; all P 0.05). Then, from the paired T-test analysis, there were no statistical significant differences in cardiovascular endurance within control group (1298.33 + 171.95, 1283.33 + 233.54; all P 0.05). But for experiment group, cardiovascular endurance showed a significant difference between pre-test and post-test data (1230.00 + 138.71, 1325.00 + 1325.00 + 181.83; all P 0.05). Hence, the circuit training program had an effect on the cardiovascular endurance component. While using the independent T-test analysis on both groups, there were not significant difference in the post test mean scores for control group and experiment group for component of cardiovascular endurance (1283.33 + 233.53, 1325.00 + 181.82; all P 0.05).All subjects do have some change, but the effects of the circuit training program were not significant enough to be conclusive. The circuit training program was effective in improve the level of cardiovascular endurance by women college students.